2011
DOI: 10.1111/j.1755-5922.2010.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel Resistance: Identifying and Overcoming a Barrier to Effective Antiplatelet Treatment

Abstract: SUMMARYClopidogrel is an inhibitor of the ADP receptor P2Y12 and platelet aggregation. It is widely used for the management of atherothrombotic disease in patients who have experienced severe vascular events such as stroke or myocardial infarction or with peripheral artery disease. However, some patients show "resistance" to clopidogrel, and show impaired inhibition of platelet aggregation. In this review, I discuss the clinical evidence of the extent of the problem, potential implications for future cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 90 publications
1
22
0
Order By: Relevance
“…A large number of elderly people with cardiovascular disease, cerebrovascular disease and chronic joint pain have been prescribed low-dose aspirin, antithrombotic drugs, NSAIDs and corticosteroids for primary or secondary prevention of cardiovascular disease, cerebrovascular disorders and arthralgia (18)(19)(20)(21)(22). In the present study, a univariate analysis focused on prescribed medications indicated that low-dose aspirin, antithrombotic drugs and corticosteroids are exacerbating factors for bleeding gastric and/or duodenal ulcers in elderly patients compared with nonelderly patients.…”
Section: Discussionmentioning
confidence: 67%
“…A large number of elderly people with cardiovascular disease, cerebrovascular disease and chronic joint pain have been prescribed low-dose aspirin, antithrombotic drugs, NSAIDs and corticosteroids for primary or secondary prevention of cardiovascular disease, cerebrovascular disorders and arthralgia (18)(19)(20)(21)(22). In the present study, a univariate analysis focused on prescribed medications indicated that low-dose aspirin, antithrombotic drugs and corticosteroids are exacerbating factors for bleeding gastric and/or duodenal ulcers in elderly patients compared with nonelderly patients.…”
Section: Discussionmentioning
confidence: 67%
“…However, some patients show resistance to clopidogrel or aspirin and impaired inhibition of platelet aggregation 12. It has been estimated that 4.2–31.0% of patients treated with clopidogrel do not achieve an appropriate level of efficacy of platelet activity,13–15 and aspirin resistance accounts for 7.8–32.0% of patients with recurrent events 16 17.…”
Section: Discussionmentioning
confidence: 99%
“…We only employed antiplatelet agent for stent-assisted procedures and aspirin with clopidogrel was given orally for three days before the procedure, referring to the guideline report of stent-assisted coil embolization 1). Individual variability of responsiveness to antiplatelet agents has been reported and the duration of antiplatelet premedication for stent-assisted coil embolization has been extended to five days with carefulness concerning about the hemorrhagic risk 4)20)25). After going through serial thromboembolic events and perceiving the low risk of hemorrhage related to antiplatelet agents, we began use of antiplatelet agent for other modes of coil embolization, which include the conventional method, multiple catheter technique, and balloon-assisted procedures 7)11)13).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no general consensus on defining aspirin and clopidogrel resistance, which hinders investigation of the prevalence. Several studies have reported a prevalence of drug resistance of 5.5-60% for aspirin and 5-44% for clopidogrel 4)5)25)…”
Section: Introductionmentioning
confidence: 99%